Oral Bioavailability and Pharmacokinetics of Nonanimal Chondroitin Sulfate and Its Constituents in Healthy Male Volunteers. Issue 3 (24th July 2018) - Volpi, Nicola; Mantovani, Veronica; Galeotti, Fabio; Bianchi, Davide; Straniero, Valentina; Valoti, Ermanno; Miraglia, Niccolò
Abstract: The pharmacokinetic profile of a new 800‐mg tablet of nonanimal chondroitin sulfate (CS) (Mythocondro®, 800‐mg tablets, Gnosis S.p.A., Italy) was investigated vs an animal CS in healthy volunteers for a total period of 48 hours. After a single 2400‐mg dose of the test and the reference formulation, total CS, the compositional disaccharides (ΔDi6S, ΔDi4S and ΔDi0S), and the overall charge density were quantified in plasma. The safety and tolerability profile after a single dose of this new nonanimal CS tablets was excellent. After baseline‐corrected concentrations, an overall greater plasma concentration was observed after 24 hours of ∼44% and after 48 hours of ∼45% from administration of nonanimal when compared to animal‐derived CS. Moreover, nonanimal CS increases the specific sulfation in the 6‐position of N ‐acetyl‐galactosamine in human plasma CS and, as a consequence, the overall charge density, reaching double values (0.91), after 48 hours compared to bovine CS and to endogenous CS. In conclusion, nonanimal CS, possessing a lower molecular weight than an animal‐derived sample, produces a greater CS concentration for a more prolonged period of time in plasma and an increase in charge density and specific 6‐sulfation of endogenous plasma CS.